Theorising unconventional climate advocates and their relationship to the environmental movement - R. M. Colvin; Robyn E. Gulliver; Xiongzhi Wang; Ajay Adhikari; Sarah J. Boddington; Kelly S. Fielding; Winnifred R. Louis (npj Climate Action)
Abstract Environmentalist-identified advocates have contributed to high levels of public support for climate action across countries. However, there remain important holdout constituencies that theory and evidence suggest are less likely to be persuaded by environmentalists, especially constituencies associated with resources and economic production, rural and regional areas, masculine norms, and conservative belief systems and politics. Emerging from these holdout constituencies, though, are some novel advocates for climate action. In this paper we theorise ‘unconventional climate advocates’ as those who combine advocacy for climate action with a social identity that departs from the prototypical environmentalist identity. Using social network analysis we show that unconventional climate advocates in Australia are peripheral to the main environmental movement, that is, the conventional advocates for climate action. We contend that unconventional advocates can broaden the social base of support for climate action, and their independence from conventional advocates – environmentalists – may aid in their efforts.